Analisis Dampak Perubahan Kurikulum 2013 Pada Saat Pembelajaran Jarak Jauh Dengan Kurikulum Merdeka Belajar - Alfiaturrohmah Alfiaturrohmah; Dewi Sophia Ariani; M. Ibaddurrahman; Fitania Syaharani E.P; Nabella Zubaida’ I.R; Az-Zahra Eldauzi; Adhea Maylila Nastiti; Bagus Setiawan (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The Covid 19 pandemic that occurred made a big change from learning that had to be offline to online, of course encountering obstacles and obstacles to adapt to changing times. After Covid is over and subsides, learning will be carried out offline again using the independent curriculum. Obstacles during distance learning start from using technology which is still unfamiliar to some people, then moving again to being independent in learning where you have to adapt to these changes. The research method uses the library study method. The research results of the change from the K13 distance learning method curriculum to the independent learning curriculum certainly have negative and positive impacts, including the positive impact, namely allowing students to learn more independently through various sources and learning media, the negative impact, among others, is that it still cannot be implemented in all area to the maximum.